The Corporate Responsibility to Respect Human Rights - United Nations (United Nations, 2012)
This Interpretive Guide on the corporate responsibility to respect human rights was developed in full collaboration with the former Special Representative. Its contents have been the subject of numerous consultations during the six years of the Special Representative’s mandate and have been reflected in many public reports and speeches, but have not previously been brought together. This Guide does not change or add to the provisions of the Guiding Principles, but provides additional background explanation to the principles directed at business enterprises, to support a full understanding of their meaning and intent. In this way, it is designed to support the process of comprehensive implementation of the Guiding Principles, as well as the development of further operational guidance to put the Guiding Principles into practice. As such, this Guide is a resource not just for business, but also for Governments, civil society, investors, lawyers and others who engage with business on these issues.